Standards and core components for cardiovascular disease prevention and rehabilitation - Cowie, Aynsley (Heart, 2019)
In 2017, the British Association for Cardiovascular Prevention and Rehabilitation published its official document detailing standards and core components for cardiovascular prevention and rehabilitation. Building on the success of previous editions of this document (published in 2007 and 2012), the 2017 update aims to further emphasise to commissioners, clinicians, politicians and the public the importance of robust, quality indicators of cardiac rehabilitation (CR) service delivery. Otherwise, its overall aim remains consistent with the previous publications—to provide a precedent on which all effective cardiovascular prevention and rehabilitation programmes are based and a framework for use in assessment of variation in service delivery quality. In this 2017 edition, the previously described seven standards and core components have both been revised to six, with a greater focus on measurable clinical outcomes, audit and certification. The principles within the updated document underpin the six-stage pathway of care for CR, and reflect the extensive evidence base now available within the field. To help improve current services, close collaboration between commissioners and CR providers is advocated, with use of the CR costing tool in financial planning of programmes. The document specifies how quality assurance can be facilitated through local audit, and advocates routine upload of individual-level data to the annual British Heart Foundation National Audit of Cardiac Rehabilitation, and application for national certification ensuring attainment of a minimum quality standard. Although developed for the UK, these standards and core components may be applicable to other countries.